Artifacts of analysis in cell line identification by short tandem repeat profiling - A. A. Malchenkova; E. N. Kosobokova (Кардиоваскулярная терапия и профилактика)
Aim. To study and describe the most common types of artifacts in detection of short tandem repeat (STR) amplicons by capillary electrophoresis and cause difficulties in interpreting the obtained STR profiles.Material and methods. Cell lines were obtained from the bioresource collection of cell lines of the Blokhin National Medical Research Center of Oncology. DNA was isolated according to the manufacturer’s instructions of the DNeasy Blood & Tissue (QIAGEN, Germany) and ExtractDNA Blood & Cells (Evrogen, Russia) kits. DNA concentration was measured using a Qubit 4.0 device (Thermo Fisher Scientific, USA) and a Qubit dsDNA BR Assay Kit (Thermo Fisher Scientific, USA). Multiplex PCR was performed using a COrDIS EXPERT26 reagent kit (Gordiz, Russia). Capillary electrophoresis of PCR products was performed on a 3500xL Genetic Analyzer (Applied Biosystems, USA). GeneMapper Software v6.0 (Thermo Fisher Scientific, USA) was used to process electrophoresis data.Results. The most well-known artifacts associated with the STR profiling and subsequent capillary electrophoretic separation of amplicons were studied. Cases of detection of these artifacts from personal practice are given. Recommendations for improving the electrophoresis pattern are given.Conclusion. The paper studies the artifacts of analysis in cell line STR profiling by capillary electrophoresis (STR-CE), which researchers encounter in laboratory practice. Common types of analysis artifacts that cause difficulties in interpreting the results obtained during STR profiling, as well as possible reasons for their occurrence, are described in detail and illustrated with examples from our own practice. Recommendations are given for reducing the number of non-specific fluorescent signals and their intensity.